IMPLEMENTASI APLIKASI KEUANGAN BERBASIS ANDROID UNTUK MEMBANTU KEGIATAN JIMPITAN DI TINGKAT RT DESA SOKARAJA KIDUL BANYUMAS - Jatmiko Indriyanto; Imam Ahmad Ashari; Anggit Wirasto (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Jimpitan is an activity at the RT (neighborhood) level, carried out every day, by collecting money from the houses in the RT 07 RW 01 village of Sokaraja Kidul. In carrying out each jimpitan activity, there are problems encountered, starting with recording errors, people who have paid are thought not to have paid, there are residents who have been registered for jimpitan but have never been withdrawn, every month there is a financial report for jimpitan, that also makes a lot of mistakes. Therefore, we propose an Android-based jimpitan financial application to help solve the problem. After trying to apply for a week, most of the problems can be resolved. Residents and RT administrators were also given questionnaires, to find out their responses to using the Android-based jimpitan financial application, the results were good, and the residents were suitable and had no difficulties.